Perigosas brincadeiras:a infância em Marcelo Mirisola e Furio Lonza - Renan Ji (Estudos de Literatura Brasileira Contemporânea)
A short novel published in 2012, Teco, o garoto que não fazia aniversário creates the expectation of a bufonic and irreverent work, given the unorthodox place that authors like Furio Lonza and Marcelo Mirisola have today in the literary scene and in terms of writing style. Imitating the structure and writing of children‘s books, the authors have subverted the genr e pointing towards an extreme revision of childhood‘s imaginary and iconography. Current traditional representations of the child have their origins in the romantic - bourgeois imaginary of late 18 th century and the beginning of the 19 th century. Those repre sentations are completely overthrown by farcical nonsense, social criticism and the violence of big cities. In the midst of a fun inversion of values (which also targets society‘s contradictions and even artistic and intellectual celebrities), Mirisola and Lonza bring the possibility of questioning and rethinking our conception of what is childhood, beyond innocence, colorful toys and ideals of education and subjectivisation.